UNVEILING WOUNDS: A TRAUMA THEORY ANALYSIS OF A LITTLE LIFE AND THE BELL JAR - Namboodiripad, Sithara Sunil (International Journal of Research -GRANTHAALAYAH, 2025)
This paper examines A Little Life by Hanya Yanagihara and The Bell Jar by Sylvia Plath through the lens of trauma theory, exploring how both novels depict psychological suffering, memory, and the long-term consequences of trauma. Relying on the works of Cathy Caruth, Judith Herman, and Dominick LaCapra, this study analyses the fragmented narratives, dissociative tendencies, and cycles of self-destruction experienced by the protagonists, Jude St. Francis and Esther Greenwood. While A Little Life presents an extended and prolonged portrait of trauma through Jude’s experiences of childhood abuse and self-harm, The Bell Jar captures Esther’s psychological deterioration within the limitations of 1950s societal expectations. Both books show the inevitable nature of past trauma, the shortcomings of outside help systems, and the conflict between resiliency and permanent psychological harm. This study emphasizes the complexity of pain, identity, and survival in modern and mid-twentieth-century literature by using trauma theory, so showing how narrative structures and character development reflect real-world trauma reactions.